Hypothalamic Inflammation as a Critical Link Between Metabolic Dysfunction and Impaired Endometrial Receptivity in Obese Polycystic Ovary Syndrome. - SUN, Chang; HAN, Yapeng; PAN, Zimeng; LI, Jing; CHENG, Xianzhuo; SUN, Miao; WANG, Ying; KUANG, Hongying (Physiological Research, 2026)
Obese polycystic ovary syndrome (PCOS) involves insulin resistance (IR) and impaired endometrial receptivity, potentially driven by hypothalamic inflammation. We investigated if inhibiting the hypothalamic Toll-like receptor 4 (TLR4)/IκB kinase β (IKKβ) pathway could ameliorate IR and improve endometrial receptivity in an obese PCOS rat model. An obese PCOS rat model was established using letrozole and high-fat diet. Rats were divided into control, PCOS, and three intervention groups: PCOS + intracerebroventricular (i.c.v.) TAK242 (central TLR4 inhibitor), PCOS + intraperitoneal (i.p.) TAK242 (systemic inhibitor), and PCOS + Metformin. We assessed hypothalamic inflammation (TLR4/IKKβ pathway), metabolic parameters (body weight, OGTT, ITT, HOMA-IR), systemic inflammation, and reproductive phenotypes. Endometrial receptivity was evaluated at pregnancy day 6 by uterine morphology, histology, pinopode development (SEM), and receptivity markers (BMP2, VEGF, IGFBP-1). The obese PCOS model successfully induced hypothalamic inflammation (activated TLR4/IKKβ pathway), systemic inflammation, profound IR, and impaired endometrial receptivity (poor decidualization, sparse pinopodes, suppressed receptivity markers). Central (i.c.v.) TAK242 administration was most effective, significantly suppressing the hypothalamic TLR4/IKKβ pathway, attenuating weight gain, normalizing insulin sensitivity, and, critically, restoring endometrial receptivity. Metformin also improved IR and receptivity, but was less potent at inhibiting the hypothalamic TLR4/IKKβ pathway. Systemic (i.p.) TAK242 showed the least efficacy, particularly on metabolic and endometrial outcomes. Hypothalamic inflammation (TLR4/IKKβ pathway) appears to be a critical mechanism linking IR and impaired endometrial receptivity in obese PCOS. Targeted central inhibition was more effective than systemic inhibition, suggesting this pathway is a novel therapeutic target.